2007
DOI: 10.1038/sj.bjp.0707150
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine upregulation of proteinase‐activated‐receptors 2 and 4 expression mediated by p38 MAP kinase and inhibitory kappa B kinase β in human endothelial cells

Abstract: Background and purpose: Up-regulation of proteinase-activated receptor-2 (PAR2) is a factor in a number of disease states and we have therefore examined the signalling pathways involved in the expression of the receptor. Experimental approach: We investigated the effects of tumour necrosis factor-a (TNF-a), interleukin-1b (IL-1b), trypsin and the PAR2 activating peptide, 2-furoyl(2f)-LIGKV-OH on both mRNA and functional expression of PAR2 in human umbilical vein endothelial cells (HUVECs). The effect of specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 57 publications
6
50
0
Order By: Relevance
“…A similar pattern was observed in SMCs from human coronary artery. Our finding reflects reports in endothelial cells that PARs are subject to differen- tial regulation 20,21 and raises the interesting possibility that individual PARs play distinct roles in various pathological conditions. The increase in PAR-4 mRNA by high glucose was sustained over the 96 hours of incubation and accompanied by increased PAR-4 protein and cell surface expression.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A similar pattern was observed in SMCs from human coronary artery. Our finding reflects reports in endothelial cells that PARs are subject to differen- tial regulation 20,21 and raises the interesting possibility that individual PARs play distinct roles in various pathological conditions. The increase in PAR-4 mRNA by high glucose was sustained over the 96 hours of incubation and accompanied by increased PAR-4 protein and cell surface expression.…”
Section: Discussionsupporting
confidence: 69%
“…Vascular PAR-3 is thought to act predominantly as a cofactor for PAR-1 in endothelium, 18 whereas PAR-4 is reportedly involved in myocardial reper- fusion injury 19 and in the endothelial response to inflammatory challenge. 20,21 In the present study in human saphenous vein SMCs, elevated glucose led to a rapid and sustained induction of PAR-4 mRNA, whereas neither PAR-1 nor PAR-3 was significantly influenced. A similar pattern was observed in SMCs from human coronary artery.…”
Section: Discussionmentioning
confidence: 89%
“…PAR2 is activated in response to the partial proteolytic cleavage of the extracellular domain by serine proteases under the influence of p38 MAP (mitogen-activated protein) kinase and by the NFκB signalling pathway, including the potentially divergent roles of the kinases inhibitory kappa B kinases (IKK)-α and -β (Ritchie et al, 2007). Inflammatory cytokines (IL-1α, TNF-α) increase mRNA expression of Par2 in disorders (Seo et al, 2011;Kamath et al, 2001;Ritchie et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Par2 gene (encodes proteinase-activated receptor 2 (PAR2), subgroup of G-protein coupled receptor family) is highly expressed in different pathologies of GIT (Seo et al, 2011;Kamath et al, 2001;Ritchie et al, 2007). PAR2 is activated in response to the partial proteolytic cleavage of the extracellular domain by serine proteases under the influence of p38 MAP (mitogen-activated protein) kinase and by the NFκB signalling pathway, including the potentially divergent roles of the kinases inhibitory kappa B kinases (IKK)-α and -β (Ritchie et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As we know, resting ECs can be mainly activated by TNF-α and IL-1β inducing to upregulate the expression level of the cytokine and cell adhesion moleculars (CAMs) via the NF-κB pathway (Modur et al, 1996;Dechanet et al, 1997;Stehlik et al, 1998;Gawaz et al, 2002;Zhou et al, 2007). Study on gene modification of ECs or other cells lines mediated by replication-defective adenovirus vectors has been broadly applied in many aspects including protein expression and RNA silence (Lin et al, 2004;Kim et al, 2007;Ritchie et al, 2007). A study showed that adenovirus vectors can stimulate maturation of dendritic cells, on which the CD40 protein expression was obviously upregulated (Morelli et al, 2000).…”
Section: Introductionmentioning
confidence: 99%